The effects of occupational differentials; trade or skilled biased technological change (SBTC)? - Said, Rusmawati; A. Hamid, Kamarul Hidayah (2010)
This paper presents sectoral levels evidence on the change of the employment share and wage premium of profesional and supervisory and technical workers in Malaysia. The paper has employed set of data comprises micro level data from the Household Income Survey (HIS) for several year during 2002-2007. In this paper we have investigated the changes in skill structure between professional and technical workers in the case of Malaysia between 2002 and 2007. Using the decomposition approach this study shown that the driving force of changes in employment structure is within sector and the effects are reflected in the movement of technology. Interestingly, the paper has two main findings from these decompositions. First, by comparing trade and technological change, we concluded that the impact of technological change is more dominant in explaining decreasing changes in the relative demand for professional workers. The impact of trade favours technical workers rather than professional workers. Across fifteen sectors that were used in this study; manufacturing, wholesale, and social work industries show clearly decreasing in demand trend for both professional and technical workers. The technological changes are the most influential factor in these changes. This result indicates that shortages in the supply of professional workers lead the government to encourage the influx of foreign workers into the country. Second, this study found that the demand for professional workers in human health, education and public admin and defense sectors show an increase in relative demand during the sample period 2002-2007. This result is consistent with the vision of the national policy in the Ninth Malaysian Plan and in line with the aspiration of producing a ‘first class mind’ community.